2018
DOI: 10.1080/02640414.2018.1428883
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of “weekend warrior” and regular physical activity patterns with metabolic syndrome and its associated diseases among Chinese rural adults

Abstract: MS: Metabolic syndrome; WC: Waist circumference; TG: Triglycerides; HDL-c: High-density lipoprotein cholesterol; BP: Blood pressure; SBP: Systolic blood pressure, DBP: Diastolic blood pressure; PA: Physical activity; JIS: Joint Interim Statement; CVD: Cardiovascular disease; ATP III: US Third Report of the National Cholesterol Education Program, the Adult Treatment Panel; IDF: International Diabetes Federation; IPAQ: International Physical Activity Questionnaire; BMI: Body mass index; CDC: the Nantong Centers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…A previous study on the relationship between metabolic syndrome and related diseases and physical activity patterns among the China rural adults was studied [ 36 ]. Our study included a group that insufficient active group as an inactive group, but in a previous study, they studied them separately.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous study on the relationship between metabolic syndrome and related diseases and physical activity patterns among the China rural adults was studied [ 36 ]. Our study included a group that insufficient active group as an inactive group, but in a previous study, they studied them separately.…”
Section: Discussionmentioning
confidence: 99%
“…It is also a cross-sectional study of rural adults over a short period of one year. Due to these differences, our study results may be slightly different, but the conclusion is that the “weekend warrior” who engaged in moderate to vigorous physical activity for high intensity was associated with a reduced incidence of metabolic syndrome [ 36 ]. In addition, this study focused on diseases such as hypertension and diabetes associated with metabolic syndrome [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…have not been consistent. A number of studies have shown a beneficial effect of weekend warrior PA patterns on the risk of all-cause mortality, CVD mortality, cancer mortality, and cardiometabolic risk factors [19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%